2020
DOI: 10.1111/gwat.13034
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of the Karst Sarabkalan Spring, Iran, and Controls of PDO and ENSO Climate Indices on It

Abstract: The Sarabkalan Spring serves as a primary water supply to irrigation and domestic use in the Sirvan Region, Iran. As it has a highly variable discharge, understanding its teleconnections with large‐scale climate variability is crucial. In this study, we first characterize the springshed and its corresponding karst aquifer system using genetic algorithm analysis on the spring discharge, water balance calculations, temporal variations of physicochemical parameters, and stable isotopes along with considering its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In that study, we found that the Pacific-based climate oscillations (PDO and, to lesser magnitude, ENSO) have a more powerful influence than the Atlantic-based oscillations (NAO and AMO) on the variability in the groundwater levels. Moreover, Rezaei (2020) explored the teleconnection between ENSO and PDO climate indices and a karst Sarabkalan Spring's discharge in the southwest of Iran with a fast-slow flow system. In this work, evidence is presented which shows a positive PDO phase coupled with El Nino increased both the precipitation and spring discharge.…”
Section: Introductionmentioning
confidence: 99%
“…In that study, we found that the Pacific-based climate oscillations (PDO and, to lesser magnitude, ENSO) have a more powerful influence than the Atlantic-based oscillations (NAO and AMO) on the variability in the groundwater levels. Moreover, Rezaei (2020) explored the teleconnection between ENSO and PDO climate indices and a karst Sarabkalan Spring's discharge in the southwest of Iran with a fast-slow flow system. In this work, evidence is presented which shows a positive PDO phase coupled with El Nino increased both the precipitation and spring discharge.…”
Section: Introductionmentioning
confidence: 99%